2001
DOI: 10.1038/90038
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in SLC11A3 is associated with autosomal dominant hemochromatosis

Abstract: Hereditary hemochromatosis (HH) is a very common disorder characterized by iron overload and multi-organ damage. Several genes involved in iron metabolism have been implicated in the pathology of HH (refs. 1-4). We report that a mutation in the gene encoding Solute Carrier family 11, member A3 (SLC11A3), also known as ferroportin, is associated with autosomal dominant hemochromatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
221
2
14

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(239 citation statements)
references
References 13 publications
2
221
2
14
Order By: Relevance
“…The median ferritin level for the whole group was 861.5 μg/L (range 17-10,000), and the median quantity of iron removed by phlebotomy was 4.25 g (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The iron removed was ≥5 g in 43 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median ferritin level for the whole group was 861.5 μg/L (range 17-10,000), and the median quantity of iron removed by phlebotomy was 4.25 g (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The iron removed was ≥5 g in 43 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Type 3 is caused by mutations in the transferrin receptor 2 gene [8], and type 4 is described as an autosomal dominant iron overload that develops from a pathogenic mutation in the SLC40a1 gene (ferroportin disease) [16,17,20]. Some authors have described mutations in HAMP and HJV as genetic modifiers of the hemochromatosis phenotype in humans [10,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25 Patients with a major form of ferroportin disease (type A) present with macrophage iron deposition and high ferritin levels despite normal transferrin saturation. 21,22 In contrast, patients with the minor form (type B) develop abnormalities, such as elevated transferrin saturation and a more severe, mixed iron overload in parenchymal and reticuloendothelial cells similar to typical hemochromatosis. 23,26 It is interesting that the urinary output of hepcidin increases in type A 27 and is normal in type B ferroportin disease.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is inherited as an autosomal dominant trait, 21,22 and occurs in populations throughout the world. 23,24,25 Patients with a major form of ferroportin disease (type A) present with macrophage iron deposition and high ferritin levels despite normal transferrin saturation.…”
Section: Introductionmentioning
confidence: 99%
“…The transferrin/transferrin receptor system is responsible for the regulated delivery of iron to most vertebrate cells (2). In the past decade, other crucial iron-regulatory genes including HFE (encoding HFE) (3), TfR2 (encoding transferrin receptor 2) (4), SLC40A1 (encoding ferroportin) (5)(6)(7)(8), HAMP (encoding hepcidin) (9)(10)(11), and HFE2 (encoding hemojuvelin or HJV) 1 (12) have been discovered, and studies of their physiological roles have revealed additional aspects of mammalian iron homeostasis. Mutations in these genes cause hereditary hemochromatosis (HH), characterized by excess absorption and storage of iron in tissues and organs, eventually leading to irreversible organ damage (13).…”
mentioning
confidence: 99%